Effects of 1-Methylcyclopropene and Modified Atmosphere Packaging on the Antioxidant Capacity in Pepper “Kulai” during Low-Temperature Storage - Chung Keat Tan; Zainon Mohd Ali; Ismanizan Ismail; Zamri Zainal (The Scientific World Journal)
The objective of the present study was to simultaneously evaluate the effect of a postharvest treatment on the pepper's antioxidant content and its ability to retain its economical value during the postharvest period. The fruits were pretreated by modified atmosphere packaging (MAP) with or without treatment with 1-methylcyclopropene (1-MCP) before cold storage at 10°C. Changes in the levels of non-enzymatic antioxidants, including the total phenolic, ascorbic acid levels and the total glutathione level, as well as enzymatic antioxidants, including ascorbate peroxidase (APX), glutathione reductase (GR), and catalase (CAT), were determined. Both treatments successfully extended the shelf life of the fruit for up to 25 days, and a high level of antioxidant capacity was maintained throughout the storage period. However, 1-MCP treatment maintained the high antioxidant capacity for a longer period of time. The 1-MCP-treated peppers maintained high levels of phenolic content, a high reduced glutathione (GSH)/oxidised glutathione (GSSG) ratio, decreased levels of ascorbic acid and CAT activity, and increased levels of APX and GR compared with the peppers that were not treated with 1-MCP. The overall results suggested that a combination of 1-MCP and MAP was the most effective treatment for extending shelf life while retaining the nutritional benefits.